If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2ax = 10 Reorder the terms: -2ax + 2x = 10 Solving -2ax + 2x = 10 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2x' to each side of the equation. -2ax + 2x + -2x = 10 + -2x Combine like terms: 2x + -2x = 0 -2ax + 0 = 10 + -2x -2ax = 10 + -2x Divide each side by '-2x'. a = -5x-1 + 1 Simplifying a = -5x-1 + 1 Reorder the terms: a = 1 + -5x-1
| x^2+144x+864=0 | | 5x-3=X-5*2 | | 18*6-5y=53 | | 0.88=ln(y) | | 5/2x-3/2=X-5 | | 3(3w+5)=-32 | | 4(f-3)=-20 | | -7/9y=3/4 | | 5(k-4)-(4k+6)=-9 | | 3(3s+8)=51 | | 4x+8+3x-2=5x+24 | | (u+2)7=21 | | (q-10)6=24 | | Cos(3x)-cos(x/2)=0 | | 15-3(x+1)=6 | | Y=cos(3x)-cos(x/2) | | (e+2)3=15 | | 22+10x=118+2x | | 10x+22=2x+18 | | 45/k=1 | | y=X^2-2x^4 | | (2x)=4/64 | | ln(x-3)+x=4 | | 3x-1=x-23 | | 5x/2-3/2=X-5 | | 4x-2+3x-3=21 | | 1/2-(x/3-x)=5/3-1/2x | | 1/2-(x/3-x)0=5/3-1/2x | | (-3x+5)(7x-6)=0 | | 3x+3+2x-4=11 | | 4x-4+6x-12=21 | | a*b=2a+3b |